Pembentukan Karakter Kesopanan melalui Pembiasaan Berbahasa Krama pada Peserta Didik Kelas 4 di Madrasah Ibtidaiyah NU 01 Purwosari Kudus - Sani, Choirun Nisa Nur (Latifah Pres, 2024)
This research is motivated by the deterioration of the polite character of students today, and there are still many students who are less able to communicate using Javanese, especially Javanese Krama. This research has a goal, namely to improve the polite character of fourth grade students at Madrasah Ibtidaiyah NU 01 Purwosari Kudus, using the habit of speaking krama in teaching and learning activities. This type of research is qualitative research with a descriptive approach. Data collection techniques were carried out by interviews, observation, and documentation. Data analysis used the Miles and Huberman flow model data analysis technique. The results showed that the manners language taught had an effect on the politeness of the students' language. The krama language is part of the Javanese language, the Javanese language is the language used for the communication tools of the Javanese people, there are ngoko lugut, ngoko alus, krama lugu, and krama inggil. Krama language is presented with the habituation method, which is tucked into every lesson, both Javanese and non-Javanese, and begins with the basic krama language. The obstacles that become obstacles; low interest, lack of motivation, intelligence of students, and also environmental influences from students.